Nicotinic Acetylcholine Receptors and Microglia as Therapeutic and Imaging Targets in Alzheimer’s Disease - Kazuyuki Takata (Molecules, 2022)
Amyloid-β (Aβ) accumulation and tauopathy are considered the pathological hallmarks of Alzheimer’s disease (AD), but attenuation in choline signaling, including decreased nicotinic acetylcholine receptors (nAChRs), is evident in the early phase of AD. Currently, there are no drugs that can suppress the progression of AD due to a limited understanding of AD pathophysiology. For this, diagnostic methods that can assess disease progression non-invasively before the onset of AD symptoms are essential, and it would be valuable to incorporate the concept of neurotheranostics, which simultaneously enables diagnosis and treatment. The neuroprotective pathways activated by nAChRs are attractive targets as these receptors may regulate microglial-mediated neuroinflammation. Microglia exhibit both pro- and anti-inflammatory functions that could be modulated to mitigate AD pathogenesis. Currently, single-cell analysis is identifying microglial subpopulations that may have specific functions in different stages of AD pathologies. Thus, the ability to image nAChRs and microglia in AD according to the stage of the disease in the living brain may lead to the development of new diagnostic and therapeutic methods. In this review, we summarize and discuss the recent findings on the nAChRs and microglia, as well as their methods for live imaging in the context of diagnosis, prophylaxis, and therapy for AD.